HUBUNGAN KUALITAS PELAYANAN PERSALINAN DENGAN KEPUASAN IBU BERSALIN DI RUMAH SAKIT ISLAM IBNU SINA BUKITTINGGI - Media Fitri; Yellyta Ulsafitri; Yessi Ardiani (HUMAN CARE JOURNAL, 2023)
The quality of normal delivery care is delivery care services that are clean and safe at every stage of labor and can meet or exceed what is expected. The quality of normal delivery care is delivery care services that are clean and safe at every stage of labor and can meet or exceed what is expected of consumers for the services that have been provided. The quality and accessibility of health service facilities can be seen from the Maternal Mortality Rate (MMR). MMR in Indonesia in 2015 has indeed decreased, namely 359 (2012) to 305 (2015) per 100,000 live births and the number of maternal deaths in Indonesia in 2019 is 4,221 cases. This research aims to see the description of patient satisfaction with delivery room services at RSI Bukittinggi, so that the elements that are maintained and repaired by the Ibnu Sina Hospital Bukittinggi can be identified and can further improve the quality of its services.